Adsorptions Studies Of Phenols Using Activated Carbons Prepared From Biomass. - Abd Rahman, Arizani (2005)
In this study, the adsorption of phenol onto two kinds of activated carbon prepared from Bamboo and Rattan were studied in batch system under varying experimental conditions; initial concentrations of phenol (25-200 mgIL), temperature (30,38 and 48°C), and pH of solution (2-12).